COMPLICATIONS RELATED TO BONE GRAFTS IN MAXILLOFACIAL SURGERIES: RISK FACTORS AND STRATEGIES TO MINIMIZE FAILURES - SYSTEMATIC REVIEW (International Seven Journal of Multidisciplinary, 2025)
Maxillofacial bone regeneration is an essential pillar in various surgical interventions, including the repair of traumatic fractures, birth defects, and tumor resections. The use of bone grafts, whether autogenous, allogene, xenogen, or synthetic, aims to restore bone continuity and promote osteogenesis. However, the success rate of these procedures can be compromised by a range of complications, such as infection, bone resorption, integration failure, and graft exposure. Such failures are often associated with multifactorial factors, including patients' clinical conditions, graft characteristics, surgical techniques employed, and environmental factors. This systematic review aims to critically analyze the most prevalent complications associated with the use of bone grafts in maxillofacial surgeries. Additionally, we will identify the most significant risk factors for failure and examine the most effective clinical and therapeutic strategies to minimize these complications. The methodology will follow strict inclusion and exclusion criteria, with an emphasis on randomized controlled trials, cohort studies, and previous reviews. The review aims to provide a comprehensive overview and up-to-date evidence that can be applied in clinical practice to optimize the outcomes of maxillofacial bone reconstructions.